(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Communities involved in free and open source activities possess special structural and processual characteristics that are conducive to innovative product development on-line. We suggest that this form of innovative, knowledge-generating, community may benefit from being seen within the framework of virtual process research using Virtual Ethnography (VE). In order to analyse the virtual ethnographic observations, innovative software research tools, such as the ‘IRC Conversation Map’, had to be devised. The investigation explored the structural and temporal dynamics of the community through the examination of interactions between members, as they unfolded in virtual space. In this way, we show how the themes that constitute the innovation process emerge from everyday routines that members of the hacker community perform. This paper contributes to the methodology of process research by exploring strategies that allow qualitative researchers to examine virtual organized activities through a process lens. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.